Psychopathy and Risk Taking among Jailed Inmates - Swogger, Marc T. (2010)
Several clinical descriptions of psychopathy suggest a link to risk taking; however the empirical basis for this association is not well established. Moreover, it is not clear whether any association between psychopathy and risk taking is specific to psychopathy or reflects shared variance with other externalizing disorders, such as antisocial personality disorder, alcohol use disorders, and drug use disorders. In the present study we aimed to clarify relationships between psychopathy and risky behavior among male county jail inmates using both self-reports of real-world risky behaviors and performance on the Balloon Analogue Risk Task (BART), a behavioral measure of risk taking. Findings suggest that associations between externalizing disorders and self-reported risk taking largely reflect shared mechanisms. However, psychopathy appears to account for unique variance in self-reported irresponsible and criminal risk taking beyond that associated with other externalizing disorders. By contrast, none of the disorders were associated with risk taking behavior on the BART, potentially indicating limited clinical utility for the BART in differentiating members of adult offender populations.